Pain Management in Albania’s Health Care System - Çuni, Zhenisa; Saliaj, Aurela (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Access to pain management is a fundamental human right. Addressing pain - whether mental, emotional, psychological, or physical - should be a primary goal for medical professionals. This article provides an overview of how the Albanian Healthcare System is structured to assist patients and examines the focus of scientific research in this area. Material and Methods: Literature review of scientific articles found on PubMed, Google Scholar, Cochrane, and Elsevier. Observation of Health Care System in Albania for 3 years. Observation of Education System in Albania for more than 15 years. Results: After literature review it became quite clear the panorama of Pain Management in Albania which totally lacks research focused on the way pain is being evaluated and monitored by nursing staff, and on non-pharmacological methods for pain relief. Regarding pain evaluation, it is traditionally evaluated through subjective and objective evaluation and there is not a unified, standardized protocol with defined tools and a schedule on how and when to evaluate pain and to address it. Until now studies and articles are focused on identifying barriers to Palliative Care, measuring Health Care System quality, and patient satisfaction. Meanwhile, Postoperative Pain Management is quite a new topic. Conclusion: In Albania’s Health Care System standardized protocols for pain assessment and management are lacking, and there is a need for continued scientific research and development in this field to address the challenges identified and offer solutions based on developed countries’ consolidated experience in pain therapy.